Mat̤laʿ al-ʿajāʾib : tarjumah-i Maʿlūmāt al-āfāq - H̱ān, Amīn-ad-Dīn (Naval Kišor, 1873)
Compendium of the wonders (ajaib) of the created world--description of the various genera of fantastic animals, angels and demons; the seven regions of the world and their geographical and mythic features. - A work on physical and general geography, with descriptions of wonders of creation, in the style of Qazwīnī's ʻAjāʼib al-makhlūqāt.